2019
DOI: 10.1021/acs.est.8b06373
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Uncertain Chinese Mercury Footprint within the Global Supply Chain Using a Stochastic, Nested Input–Output Model

Abstract: A detailed understanding of the mercury footprint at subnational entity levels can facilitate the implementation of the “Minamata Convention on Mercury”, especially for China, the largest mercury emitter worldwide. Some provinces of China have more than 100 million people, with economic activities and energy consumption levels comparable to those of smaller G7 countries. We constructed a stochastic, nested multiregion input–output (MRIO) model, which regionalized the China block in the EXIOBASE global-scale MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Due to the limited quality and availability of mining-related water and land use data, future work should also improve mining-related water and land impacts. Moreover, future research is needed to analyze this study's results for uncertainty, which could be addressed by extending the approach of Lenzen al [81] and Zhang et al [82] to this study's methodology and database.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limited quality and availability of mining-related water and land use data, future work should also improve mining-related water and land impacts. Moreover, future research is needed to analyze this study's results for uncertainty, which could be addressed by extending the approach of Lenzen al [81] and Zhang et al [82] to this study's methodology and database.…”
Section: Discussionmentioning
confidence: 99%
“…28−30 These studies highlight three main issues: (1) treating a very large nation (e.g., China, which drives ∼30% of global material flow) as a homogeneous entity within a global multiregional input−output table (GMRIO) may mean researchers are unable to analyze important dynamics in the trade; 5,20,31 (2) it may bring bias to national results in total, 26,32−34 and (3) policymakers may struggle to convert messages from global and national analyses to regional strategies and targets. 18,22,24,25,31,32 Early EE-IO studies often used a single-region input−output (SRIO) table. However, to be able to account for trade, researchers had to make certain assumptions, e.g., that imports were produced with the same technology as the importing country (i.e., that an electronic product imported from Japan into the U.S.A. is assumed to have been produced with U.S. technologies rather than Japanese).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have highlighted that the use of the TSA approach requires further analysis and investigation. 16,24,41 Overcoming this TSA simplification presents a key data and knowledge gap. Previous economic studies showed that the trade structure among domestic regions and foreign countries are essential to subnational modeling.…”
Section: Introductionmentioning
confidence: 99%
“…f is a vector of environmental pressure intensities of all the sectors accounted for, or PBA as denoted in other research (Z.‐M. Chen et al., 2018; Lindner et al., 2013; Södersten et al., 2018; H. Zhang et al., 2019). I is an identity matrix.…”
Section: Methodsmentioning
confidence: 99%